Nitrogen-fixing, phosphate-potassium-mobilizing ability of Rahnella bacteria isolated from wheat roots - Shakirov, Z. S.; Mamanazarova, K. S.; Yakubov, I. T.; Zakiryaeva, S. I.; Khamidova, K. M. (Regulatory Mechanisms in Biosystems, 2022)
As the number of people on earth increases, so does the need for food. Providing the population with environmentally friendly agricultural food is one of the urgent problems of our time. Currently, the main direction of modern organic farming is the use of biofertilizers. Bacterial preparations are capable of influencing the physiological processes of plants in small quantities, leading to increase in plant productivity. The objective of this work was to study rhizobacteria associated with wheat roots. For this purpose, we took more than 100 isolates of rhizobacteria from the rhizosphere and root surface of wheat plants grown in irrigated fields of Tashkent, Syrdarya, Andijan, Kashkadarya regions. Rhizobacteria were grown on nutrient media of Döbereiner, Ashby, Pikovsky, and Zack, and 25 isolates of associative rhizobacteria were selected based on the characteristics of absorption of molecular nitrogen, mobilization of phosphorus and potassium. They actively dissolved Сa3(PO4)2 and KAlSiO4 for 3 days. They were found to produce organic acids. In organic farming, nitrogen-fixing, phosphorus- and potassium-mobilizing rhizobacteria are of great practical importance, while our experiments on obtaining biological products are considered as an environmentally friendly and cost-effective way to increase crop yields. From the surface of wheat roots grown in different zones of Uzbekistan, when screening for nitrogen fixation, we selected 3 isolates with acetylene reductase activity of 79–91 nmol C2H4/flacon/24h. We determined that bacteria completely mobilized phosphate, forming 100% acid when grown in a medium containing Ca3(PO4)2 for 5 days. The ability of the bacteria to mobilize potassium was studied on a nutrient KAlSiO4-containing medium. The bacteria were observed to mobilize potassium, forming 90–100% acid within 15 days. Based on the study of the 16S rRNA gene of bacteria, we identified rhizobacteria UT3, UT4, and UT9 as Rahnella aquatilis.